Ideologi Pancasila Sebagai Ideologi Terbuka - Azizurohim, Azizurohim (Maliki Interdisciplinary Journal, 2026)
Pancasila as the ideology of the Indonesian nation has a unique character because it is open, dynamic, and adaptive to the development of the times. As an open ideology, Pancasila is not dogmatic or rigid, but provides space for interpretation, update, and application of its values according to the needs of society without eliminating its basic principles. This research aims to analyze the concept of openness of the Pancasila ideology, its implications for national development, and the challenges faced in maintaining its relevance in the midst of social, political, and global changes. The research method uses a qualitative approach through literature studies on various scientific works and official documents related to Pancasila. The results of the study show that the openness of Pancasila strengthens its function as a guideline for the life of the nation and state because it is able to accommodate the values of democracy, human rights, and the development of science. However, the nature of this openness also raises the potential for interpretation deviations that can shift the fundamental values of Pancasila. Therefore, a deep understanding, continuous Pancasila education, and social control mechanisms are needed to ensure that the reinterpretation of values takes place within the corridor of the basic principles of Pancasila. This study emphasizes that Pancasila as an open ideology remains relevant as the foundation of national life as long as its meaning is carried out contextually but still based on its original values.